Current perspectives on the non-destructive characterization of sweeteners (Agroindustrial Science, 2026)
The growing concern for food quality, authenticity, and safety has driven the development of reliable analytical methods for the detection and quantification of both natural and synthetic sweeteners. In this context, spectroscopic techniques have gained prominence due to their speed, sensitivity, and non-destructive nature, positioning them as key tools for food product analysis. This review examines current scientific trends in sweetener analysis through a bibliometric approach, describes the theoretical foundations and evolution of technologies such as FTIR, NIR, UV-Vis, and Raman spectroscopy, and explores their specific applications in the identification and quantification of these compounds. Additionally, the review discusses the implications of these methodologies for quality control systems and food safety, highlighting their strategic role in prevention of fraud, consumer protection, and the improvement of traceability and transparency in processed food products.
Keywords: Chemometrics; Adulteration; Multicomponent analysis; Authentication